On Restructuring, Regulation, and Competition in Utility Industries: Experience in the United Kingdom and Implications for Latin America - Andrew Powell (Inter-American Development Bank, Office of the Chief Economist, 1996)
There are two similarities between the utility privatization programs of the UK and Latin America. Privatization has largely consisted of the transfer of industry-dominant, state companies into the private sector, often with statutory monopoly powers. In addition, the extensive use of price cap rather than rate-of-return regulation. A difference is that, arguably, the UK tried to create a fair but flexible regulatory policy by establishing a set of individual industry regulators somewhat independent from the government with considerable discretionary powers.
Keywords: 330